The Internalization of Multicultural Education and Religious Moderation in Strengthening the Character of University Students in Lampung - Subandi; Sa’idy (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
Religious moderation and multiculturalism in the era of digitalization serve as regulators of student behavior to counter the rapid development of digitalization in the modern age. This research aims to examine the internalization of multicultural education and religious moderation in strengthening the character of students in Indonesia. Using a qualitative approach, data was collected through in-depth interviews, observations, and document analysis, and then analyzed through data display, coding, and interpretation, ultimately leading to conclusions based on the qualitative analysis of Miles & Huberman. The results of the study indicate that the internalization of religious moderation and multiculturalism in shaping student character can be achieved through the following steps: 1) integration of multicultural content and religious moderation in the curriculum, 2) activities within student learning, 3) habituation of activities in student life, 4) equal opportunities for learning without gender discrimination, and 5) an inclusive academic culture that is open and based on respect for diversity, as well as social structure. Learning activities on campus contribute to the formation of student character in higher education, supported by the alignment of objectives, materials, and learning strategies, leading to the strengthening of social communities within the cohesive student environment.